Fisiognomica emozionale. Affordances, estasi, atmosfere (Lebenswelt. Aesthetics and philosophy of experience., 2015)
Through an atmospherological approach, primarily inspired by the so-called Aisthetik or New Aesthetics (Gernot Böhme) and the New Phenomenology (Hermann Schmitz), the paper defines the atmospheric perception as a first pathemic impression and investigates the relationship between this kind of perception and the expressive qualities of the surrounding spaces. The aim is to understand atmospheres as (amodal, transmodal, sinaesthetic) affordances that permeate the lived space, namely as ‘ecological’ and affective invites or meanings which are ontologically rooted in things and quasi-things.